Knowledge, attitude and practice of food handlers towards chicken hygiene and food safety in chicken restaurants in Ouagadougou, Burkina Faso - Gemeda, Biruk A.; Assefa, Ayalew; Dione, Michel M.; Ilboudo, Guy S.; Lallogo, Valérie R.; Grace, Delia; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2023)
Objective Chicken is the primary animal source food consumed in street restaurants in Burkina Faso. In most of these restaurants, slaughtering, processing, and cooking practices are carried out with poor hygienic conditions. A cross-sectional survey was carried out to assess food safety knowledge, attitude, and hygienic practice of food handlers in chicken outlets of Ouagadougou.